Eva Malina Simatupang ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK-ETAP PADA KOPDIT CU. KARYA NYATA PEMATANG SIANTAR - Eva Malina Simatupang (LPPM Universitas Putera Batam, 2018)
The generally accepted Financial Accounting Standards are considered to be complicated to apply to business entities that do not have public accountability. Based on this IAI issued SAK ETAP (Financial Accounting Standards Entity Without Public Accountability) that can accommodate the accounting needs for entities that do not have public accountability. SAK ETAP is a standard that regulates the accounting treatment of MSMEs and cooperatives in Indonesia, but all cooperative activities are also guided by the latest laws and government regulations issued by the relevant ministers in this case the Regulation of the Minister of Cooperatives and Small and Medium Enterprises (K -UKM) of the Republic of Indonesia No. 12 of 2015, concerning General Guidelines for Cooperative Accounting. This study aims to analyze the application of SAK ETAP in the financial statements Kopdit CU. The Real Work of Pematang Siantar. Kopdit CU. The real work of Pematang Siantar is a cooperative in the saving and loan business. The method of this research is comparative descriptive analysis. It was found that the financial statements of CU Kopdit. The real work of Pematang Siantar 2017 has not presented the Financial Statement in accordance with SAK ETAP.